Effect of multiple pressures by magnetic pulsed compaction (MPC) on the density of gas-atomized Al–20Si powder - Park, Hyo-Young; Kilicaslan, M. Fatih; Hong, Soon-Jik (Elsevier BV, 2012)
Abstract Rapidly solidified Al-20 wt.%Si alloy powders with particle size of ~ 106 μm in diameter were fabricated by gas atomization, and the powder compaction was performed by using magnetic pulsed compaction. Multiple way experiments were carried out on Al–Si powders with varying pressing time, weight and intensity of initial and final pressures. Effects of process parameters during multiple pressing such as, number of repeated pressing, initial pressure, and final pressure, on the density were investigated. It was found that density decreases with increasing weight of powder poured to the die, but it enhances with increasing pressure. The last compaction pressure has a more dominant effect on the density than the initial compaction pressure in magnetic pulsed compaction process. With increasing the number of repeated pressing, the density of the compacted product increases.